Comparative Analysis of Groundwater Quality Parameters to Identify Contamination Patterns and Their Causes - Nurdin, deden Muhamad (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
The purpose of this study was to analyze and compare groundwater quality parameters across land use zones to identify contamination patterns and underlying causes. The materials used in this study were collected from empirical studies conducted on 15 sites representing agricultural, industrial, and residential areas and analyzed for physical and chemical parameters including pH, total dissolved solids (TDS), heavy metals, and major ions. The method used in this study was comparative analysis with a qualitative approach. The results showed significant spatial variability influenced by anthropogenic activities and natural geochemical processes. Agricultural areas showed increased levels of TDS and nitrate, industrial areas showed heavy metal contamination, and residential areas showed higher turbidity. Statistical analysis revealed correlations between contamination sources and water quality parameters. The results underline the need for targeted management strategies to reduce contamination and ensure groundwater sustainability. The results identified significant spatial variability in groundwater quality across the 15 sites, influenced by natural hydrogeochemical processes and human activities. Agricultural areas showed high levels of total dissolved solids (TDS), electrical conductivity (EC), and nitrate due to fertilizers and irrigation. Industrial areas experienced heavy metal contamination, including lead and cadmium, exceeding WHO limits, while residential areas showed moderate contamination with occasional turbidity and nitrate problems. These results emphasize the impact of local human activities on groundwater quality and the need for targeted mitigation efforts.